Performance and Perception in Prefab Housing: An Exploratory Industry Survey on Sustainability and Affordability. (2017) - Dave, Malay; Watson, Bruce; Prasad, Deo
Abstract: Provision of adequate and affordable housing is a major challenge in both emerging and industrialised countries. With increasing urgency for addressing climate change and other environmental issues these habitats will need to be environmentally sustainable too. Conventional construction, especially in dense urban centres and in rural or remote areas, is putting great pressures on cost and resource efficiency and is compelling the industry and governments globally to question the approach of business-as-usual. Prefabrication or off-site construction can offer great opportunities for both environmental and economic performance and hence is emerging as an attractive alternative to on-site construction. Although in the established markets the share of prefabrication in overall construction output remains strong, in many countries including Australia it still remains in its infancy. In order to enhance the profile of prefab housing and effectively develop high performance sustainable and affordable housing it is vital that first the needs and perceptions of the industry on these issues are adequately studied. This paper relates to the first of a two part research project aimed at exploring the makeup of the prefab housing industry and identifying various challenges and opportunities. The study was conducted as an international industry survey in which barriers, opportunities, performance and perceptions of sustainability and affordability were explored. The paper presents the results of this survey. Based on a cross-sectional analysis the responses are compared and categorised. Among other things the findings highlight the gaps in our understanding of the relationship between sustainability and affordability. This research contributes to the discourse on the need to better understand the role of design and design decision making for developing high performance prefab housing.